Pengaruh Online Customer Review, Store Atmosphere dan Kualitas Pelayanan terhadap Kepuasan Konsumen Gen Z Surabaya Timur pada Brain Coffee Surabaya - Abiyyah Dyastiningrum Ni’mah; Diana Juni Mulyati; Ni Made Ida Pratiwi (Politeknik Kampar, 2025)
This study aims to determine the effect of online customer reviews, store atmosphere, and service quality on consumer satisfaction of Generation Z at Brain Coffee Surabaya. The background of this study is based on the increasing competition of coffee shop businesses in the city of Surabaya and the importance of understanding the preferences and satisfaction of Gen Z consumers who are a potential market share. This study uses a quantitative method with a descriptive approach. The population in this study is Generation Z who have purchased and visited Brain Coffee Surabaya with a sample size of 100 respondents. Data were collected by distributing questionnaires using Google-Form to respondents who have visited Brain Coffee and are part of Generation Z in East Surabaya. This study uses IBM SPSS version 25. Based on the results of this study, it shows that the variables Online Customer Review (X1), Store Atmosphere (X2), and Service Quality (X3) have a significant effect on consumer satisfaction of Gen Z at Brain Coffee both partially and simultaneously.